(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article, based on the analysis of scientific views of scientists, argues that the state of ensuring legality during the administration of justice is the degree of compliance with the requirements of the Constitution and laws of Ukraine, as well as the principles of the rule of law and legality by judges during the administration of justice. It is generalized that the state of ensuring legality during the administration of justice is the degree of compliance with the requirements of the Constitution and laws of Ukraine, as well as the principles of the rule of law and legality by judges during the administration of justice. In addition, the state of ensuring legality reflects the level of public trust in the judiciary as a whole. It is noted that the state of ensuring legality is influenced by various factors, such as: the number of cases considered by a judge (judge workload); uniform distribution of judges across the territory of Ukraine in accordance with the population; openness of judicial consideration of cases to the public (publicity, openness and transparency of the judicial system); the existence of a high-quality personnel selection system that allows a person with appropriate qualifications in the legal field and high moral and psychological characteristics of the personality to hold the position of judge, which excludes legal nihilism and low personal culture; rapid investigation of possible disciplinary offenses, including responding to reports on social networks and other media about corruption and other offenses by individual judges; the presence of a clear mechanism for dismissing a judge from office if he violates anti-corruption legislation. It was stated that the current state of ensuring legality in the administration of justice can hardly be called satisfactory, which is due to the excessive workload of judges, their uneven distribution (deficit of judicial personnel), high level of corruption in society, etc.